A Comparative Study of the Influence of Online Store Perception and Offline Store Perception on Purchase Decisions with Customer Satisfaction as a Mediating Variable in the Islamic Business Perspective - Eksanti, Rindi Julia; Hayati, Mardhiya; Susanti, Yeni (Jurnal Ilmiah Sumber Daya Manusia, 2025)
This study aims to examine and compare the influence of online store perception and offline store perception on consumer purchasing decisions at Sociolla in Bandar Lampung, considering customer satisfaction as a mediating variable from an Islamic business perspective. Employing a quantitative approach with a descriptive method, the research focuses on Sociolla consumers residing in Bandar Lampung who have made purchases both online and offline. Data collection was conducted through questionnaires, and the analysis utilized Structural Equation Modeling (SEM) based on Partial Least Squares (PLS) with the assistance of SmartPLS software. The findings reveal that offline store perception has a positive and significant effect on customer satisfaction and on purchasing decisions. Conversely, online store perception does not significantly affect customer satisfaction or purchasing decisions. Customer satisfaction significantly mediates the effect of offline store perception on purchasing decisions, but does not mediate the effect of online store perception. In conclusion, offline store perception positively and significantly influences purchasing decisions, mediated by customer satisfaction, while online store perception does not have a significant impact and is not mediated by customer satisfaction. From an Islamic business perspective, these results underscore the importance of honesty, transparency, and quality service in fostering customer satisfaction and encouraging purchasing decisions. However, the study has limitations, including its reliance on the subjective perceptions of respondents, which may be influenced by personal experiences, and its focus on consumers in Bandar Lampung, which restricts generalizability. Additionally, the research has not explored other variables such as brand loyalty or perceived value.